ALMIJIRAH’S PROCESS OF COMBINING ISLAMIC KNOWLEDGE AND ENTREPRENEURSHIP SKILLS FOR SELF-RELIENCE IN NIGERIA - Hauwa Talatu Yusuf; Atiku Garba Yahaya (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Islam emphasises educating both men and women alike. Muslim women from the first generation of Islam have shown deep interest in studying the Hadith of the Prophet (SAW), and have contributed a great deal to the development of the science of Hadith. They have contributed in academia, the business and financial sectors, medicine and science, and numerous other fields of knowledge. This paper intends to describe the process followed by the Muslim female Almajirah in the acquisition of Islamic knowledge and entrepreneurship skills in Niger State, Nigeria. The data collected for this work in terms of the number of Madaris visited, the number of students and other relevant information collected were presented in tabular format. The data presented provides more information on the coverage of the study area as conducted in this research. The method of data collection is oral interview complimented with observation. The experiences of the Muslim female Almajirah under studies, and as an entrepreneur, of this system of learning were also narrated in descriptive term. It is concluded that the Muslim female Almajirah, if given the right training and conducive environment will be able to contribute positively in all spheres of life endeavour; and especially in terms of the spread of Islamic knowledge, moral training and self-reliance through acquisition of religious knowledge and a viable trade that can sustain her to enable her fend for her needs. Islam menekankan mendidik baik laki-laki maupun perempuan. Wanita Muslimah dari generasi pertama Islam telah menunjukkan minat yang mendalam untuk mempelajari Hadits Nabi (SAW), dan telah memberikan kontribusi yang besar bagi pengembangan ilmu Hadits. Mereka telah memberikan kontribusi di bidang akademis, bisnis dan sektor keuangan, kedokteran dan ilmu pengetahuan, dan berbagai bidang pengetahuan lainnya. Makalah ini bermaksud untuk mendeskripsikan proses yang diikuti oleh Almajirah wanita Muslim dalam perolehan pengetahuan Islam dan keterampilan kewirausahaan di Negara Bagian Niger, Nigeria. Data yang dikumpulkan untuk pekerjaan ini dalam hal jumlah Madaris yang dikunjungi, jumlah siswa dan informasi relevan lainnya yang dikumpulkan disajikan dalam format tabel. Data yang disajikan memberikan informasi lebih lanjut tentang cakupan wilayah studi seperti yang dilakukan dalam penelitian ini. Metode pengumpulan data adalah wawancara lisan yang dilengkapi dengan observasi. Pengalaman Almajirah perempuan Muslim yang sedang menempuh studi, dan sebagai seorang wirausahawan, sistem pembelajaran ini juga diriwayatkan secara deskriptif. Disimpulkan bahwa Almajirah Muslimah, jika diberikan pelatihan yang tepat dan lingkungan yang kondusif akan mampu memberikan kontribusi positif dalam segala bidang kehidupan; dan terutama dalam hal penyebaran pengetahuan Islam, pelatihan moral dan kemandirian melalui perolehan pengetahuan agama dan perdagangan yang layak yang dapat menopangnya untuk memenuhi kebutuhannya.